2013
DOI: 10.1007/s12311-013-0537-0
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Emotional Facial Expression and Prosody Discrimination Due to Ischemic Cerebellar Lesions

Abstract: A growing literature points to a specific role of the cerebellum in affect processing. However, understanding of affect processing disturbances following discrete cerebellar lesions is limited. We administered the Tübingen Affect Battery to assess recognition of emotional facial expression and emotional prosody in 15 patients with a cerebellar infarction and 10 age-matched controls. On emotional facial expression tasks, patients compared to controls showed impaired selection and matching of facial affect. On p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 22 publications
6
34
0
2
Order By: Relevance
“…Patients with left lateral but not medial cerebellar tumors including Crus I exhibited deficits in perceiving human motion (Sokolov et al, 2010; Figure 1B). On the other hand, in 15 patients tested 1-5 weeks after cerebellar stroke, no significant overall impairments were found in perception of emotions from prosody and photographs of faces (Adamaszek et al, 2014). However, sub-analyses revealed difficulties in selecting the facial expression matching a specific emotion, naming the emotional expression of prosody that may or may not correspond to the semantic content, and matching faces to prosody with similar emotional expression.…”
Section: Socio-cognitive Deficits In Patients With Focal Cerebellar Lmentioning
confidence: 82%
“…Patients with left lateral but not medial cerebellar tumors including Crus I exhibited deficits in perceiving human motion (Sokolov et al, 2010; Figure 1B). On the other hand, in 15 patients tested 1-5 weeks after cerebellar stroke, no significant overall impairments were found in perception of emotions from prosody and photographs of faces (Adamaszek et al, 2014). However, sub-analyses revealed difficulties in selecting the facial expression matching a specific emotion, naming the emotional expression of prosody that may or may not correspond to the semantic content, and matching faces to prosody with similar emotional expression.…”
Section: Socio-cognitive Deficits In Patients With Focal Cerebellar Lmentioning
confidence: 82%
“…Moreover, neuroimaging and neurostimulation studies have shown the involvement of the cerebellum in conscious processing of emotional facial expressions [69,81,85].…”
Section: Cerebellar Involvement In the Conscious Component Of Emotionsmentioning
confidence: 99%
“…Clinical studies in patients with cerebellar damage have also highlighted the involvement of the cerebellum in emotional recognition, allowing proper social cognition regardless of stimulus (visual or auditory), particularly for negative emotions [69,72], and in more complex social cognition domains. This has become known as the Theory of Mind (ToM) [73,76,77].…”
Section: Cerebellar Involvement In the Conscious Component Of Emotionsmentioning
confidence: 99%
“…In animals (e.g., mice and rodents), the posterior vermis orlimbicvermis [62]playsa centralrolein fear conditioning, mediatedbypain;inhumans,the cerebellar areas involved could also include posterior cerebellar hemispheres together with the vermis as suggestedby our results. Adamaszek et al provided preliminary evidence of that in a groupof cerebellar stroke patients with a specific impairment for emotionalprocessing and associated lesions in the posterior cerebellum [65]. This could be related to an integrated processing in emotion and cognition in humans [66]: an evolutionary frontalization of the emotion parallel to the frontal lobedevelopment, well representedbythis cerebellar network.…”
Section: Cluster VIImentioning
confidence: 99%